Hubungan Kepercayaan Diri dengan Keterampilan Bertanya Siswa dalam Belajar - Mawaddah, Mawaddah; Linda Fitria; Popi Radyuli (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Confidence is something that is priceless. By having self-confidence, one can do anything with the belief that it will work. If it turns out that a person fails, they don't necessarily give up, but they still have enthusiasm, remain realistic, have motivation and then steadily try again. Asking skill is an attempt to prepare oneself to ask to understand something that is not yet understood. This research aims to determine the relationship between self-confidence and students' questioning skills in learning at SMK N 9 Padang even semester of the 2022/2023 school year. The type of research used is quantitative method. The study population amounted to 440 people enrolled in the 2022/2023 school year, with a sample of 210 people taken using proportional rondom sampling technique. This research examines the relationship between self-confidence and questioning skills. The instrument used in data collection in this research was a questionnaire prepared according to the Likert scale model. Data analysis was carried out using a statistical program on the SPSS 24 computer and Microsoft Excel. Based on the results of the hypothesis, the rcount value is 0.960 while the rtable value is 0.135 because the value of r count is greater than r table (0.960> 0.135), there is a significant positive relationship between self-confidence and students' questioning skills in learning at SMK N 9 Padang even semester of the 2022/2023 school year.